Hot-melt Preparation of a Non-biodegradable Peptide Implant: A Proof of Principle - D128;™Hondt, Matthias; Verbeke, Frederick; Wuytens, Pieter; Skirtach, Andre; De Spiegeleer, Bart; Wynendaele, Evelien (Protein and Peptide Letters, 2019)
Background: Both biodegradable and non-biodegradable peptide-loaded implants are already developed for the long-term treatment of patients, thereby reducing the frequency of drug administration. To further improve peptide formulation, extending the scope of implant-based drug delivery systems towards other polymers and processing techniques is highly interesting. Objective: In this study, as a proof-of-principle, the feasibility of hot-melt processing of a peptide active pharmaceutical ingredient was assessed by developing a non-biodegradable poly(ethylenevinyl acetate) (33% VA) implant loaded with 20% (w/w) buserelin acetate. Methods: Cross-sectional implant characterization was performed by Raman microscopy. The stability of buserelin acetate in the polymeric matrix was evaluated for 3 months under ICH stability conditions and the quantity as well as the degradation products analyzed using LC-UV methods. An in vitro dissolution study was performed as well and buserelin acetate and its degradants analyzed using the same chromatographic methods. Results: No significant quantities of buserelin acetate-related degradation products were formed during the hot-melt preparation as well as during the stability study. Together with the consistent buserelin acetate assay values over time, chemical peptide stability was thus demonstrated. The in vitro buserelin acetate release from the implant was found to be diffusion-controlled after an initial burst release, with stable release profiles in the stability study, demonstrating the functional stability of the peptide implant. Conclusion: These results indicate the feasibility of preparing non-biodegradable peptide-loaded implants using the hot-melt production method and may act as a proof of principle concept for further innovation in peptide medicinal formulations.
Keywords: hot-melt process